Pengaruh Kualitas Produk, Kualitas Layanan, dan Harga Terhadap Kepuasan Konsumen: Studi pada Toko Bangunan ”Sido Mulyo” Yogyakarta - Vicky Fatur Rahman; Agus Abdurrahman (Jurnal Bisnis Kreatif dan Inovatif, 2024)
The purpose of this study is to evaluate (1) the impact of product quality on customer satisfaction, (2) the contribution of service quality to customer satisfaction, and (3) the effect of price on customer satisfaction. This study uses a quantitative approach with participants consisting of customers who have made purchases and visited Sido Mulyo Building Store in Yogyakarta, totaling 90 selected respondents based on the calculation by Hair et al. (2010). Data were analyzed using multiple linear regression with the IBM SPSS Statistic 22 analysis tool. The findings of this study indicate that (1) product quality has a positive and significant contribution to customer satisfaction at Sido Mulyo Building Store Yogyakarta, (2) service quality also has a meaningful and significant impact on customer satisfaction at Sido Mulyo Building Store Yogyakarta, and (3) price has a positive and significant effect on customer satisfaction at Sido Mulyo Building Store Yogyakarta.